2020
DOI: 10.32890/mmj.20.2016.9039
|View full text |Cite
|
Sign up to set email alerts
|

Does Global Financial Crisis Integrate the Regional Market in Asia More Strongly?

Abstract: The aim of this paper is to analyze whether the worldwide financial crisis integrates the regional markets in Asia more strongly. Secondly, it is also to examine whether the integration of regional markets in Asia necessarily leads to a weak form of market efficiency. To examine this we have considered the different broad based and liquid stock indices such as the Sensex and BSE 100 from the Bombay Stock Exchange; the S&P CNX Nifty from the National Stock Exchange, representing India; the Hang Seng Index f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The relationship between stock prices and macroeconomic dynamics has been studied extensively (Al‐Awadhi, Al‐Saifi, Al‐Awadhi, & Alhamadi, 2020; Ali, Alam, & Rizvi, 2020; Dhingra, Gandhi, & Bulsara, 2016; Ichev & BakerMarinc, 2018; Jain & Biswal, 2016; Katechos, 2011; Li, Su, Chang, & Ma, 2018; Lin & Fu, 2016; Mallick & Mishra, 2019; Mishra, 2004; Mishra, Rath, & Dash, 2020; Vyas, 2014; Vyas & Mishra, 2016; Vyas, Prasad, & Mishra, 2011; Wong, 2017). From these studies, the impact of pandemics (see Al‐Awadhi et al, 2020; Ali et al, 2020; Ichev & BakerMarinc, 2018) gold and crude oil prices (see Jain & Biswal, 2016) demand for money, short term interest rate, net foreign equity flows, and the exchange rate (See Dhingra et al, 2016; Mishra, 2004; Vyas, 2014; Vyas et al, 2011; Vyas & Mishra, 2016) are shown to influence India's stock market. The second strand of studies shows stock prices are driven by operating earnings, dividend, book value and net profit in the US market (Collins, 1957).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between stock prices and macroeconomic dynamics has been studied extensively (Al‐Awadhi, Al‐Saifi, Al‐Awadhi, & Alhamadi, 2020; Ali, Alam, & Rizvi, 2020; Dhingra, Gandhi, & Bulsara, 2016; Ichev & BakerMarinc, 2018; Jain & Biswal, 2016; Katechos, 2011; Li, Su, Chang, & Ma, 2018; Lin & Fu, 2016; Mallick & Mishra, 2019; Mishra, 2004; Mishra, Rath, & Dash, 2020; Vyas, 2014; Vyas & Mishra, 2016; Vyas, Prasad, & Mishra, 2011; Wong, 2017). From these studies, the impact of pandemics (see Al‐Awadhi et al, 2020; Ali et al, 2020; Ichev & BakerMarinc, 2018) gold and crude oil prices (see Jain & Biswal, 2016) demand for money, short term interest rate, net foreign equity flows, and the exchange rate (See Dhingra et al, 2016; Mishra, 2004; Vyas, 2014; Vyas et al, 2011; Vyas & Mishra, 2016) are shown to influence India's stock market. The second strand of studies shows stock prices are driven by operating earnings, dividend, book value and net profit in the US market (Collins, 1957).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between stock prices and macroeconomic dynamics has been studied extensively (Al-Awadhi, Al-Saifi, Al-Awadhi, & Alhamadi, 2020;Ali, Alam, & Rizvi, 2020;Dhingra, Gandhi, & Bulsara, 2016;Ichev & BakerMarinc, 2018;Jain & Biswal, 2016;Katechos, 2011;Li, Su, Chang, & Ma, 2018;Lin & Fu, 2016;Mallick & Mishra, 2019;Mishra, 2004;Mishra, Rath, & Dash, 2020;Vyas, 2014;Vyas & Mishra, 2016;Vyas, Prasad, & Mishra, 2011;Wong, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation